2019
DOI: 10.1590/1414-431x20198338
|View full text |Cite
|
Sign up to set email alerts
|

Burden, access, and disparities in kidney disease

Abstract: This article was published in Kidney International volume 95, pages 242–248, https://doi.org/10.1016/j.kint.2018.11.007 , Copyright World Kidney Day 2019 Steering Committee (2019) and is reprinted concurrently in several journals. The articles cover identical concepts and wording, but vary in minor stylistic and spelling changes, detail, and length of manuscript in keeping with each journal's style. Any of these versions may be used in citing this article. Note that all authors contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
0
18
0
3
Order By: Relevance
“…Thus, global efforts to increase awareness of CKD and its risk factors have mobilized several countries to tackle this chronic condition and its complications, demanding that governments design public policies that can support early identification and treatment programs, with emphasis on preventive measures that slow the progression of renal function loss 6 . The implementation of a public policy for preventing kidney diseases in the world is recent, dating from 2002, when the National Kidney Foundation published the first guideline for CKD diagnosis and treatment, in its document Kidney Disease Outcomes Quality Initiative (K/DOQI) 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, global efforts to increase awareness of CKD and its risk factors have mobilized several countries to tackle this chronic condition and its complications, demanding that governments design public policies that can support early identification and treatment programs, with emphasis on preventive measures that slow the progression of renal function loss 6 . The implementation of a public policy for preventing kidney diseases in the world is recent, dating from 2002, when the National Kidney Foundation published the first guideline for CKD diagnosis and treatment, in its document Kidney Disease Outcomes Quality Initiative (K/DOQI) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Mediante o exposto, esforços globais para aumentar a consciência da DRC e seus fatores de risco têm mobilizado vários países para o enfrentamento dessa condição crônica e suas complicações, demandando dos governantes o delineamento de políticas públicas que possam respaldar programas de identificação e tratamento precoce, com ênfase nas medidas preventivas que retardam a velocidade de progressão da perda da função renal 6 . É importante destacar que a implantação de uma política pública na prevenção das doenças renais no mundo é recente, datada de 2002, quando foi publicada a primeira diretriz para diagnóstico e tratamento da DRC pela National Kidney Foundation , em seu documento Kidney Disease Outcomes Quality Initiative (K/DOQI) 7 .…”
Section: Introductionunclassified
“…This finding is in line with various studies that reported individuals who consumed mostly saturated fat were deemed to have a higher risk of reduced renal function, and those with higher levels of high density lipoprotein (HDL) cholesterol were associated with a lower risk for CKD. [39][40][41][42] Thus, reducing the consumption of palm oil and replacing with vegetable oil could help in the prevention of the disease. Dietary counseling for patients with CKD who are under follow-up could help to slow progression of the diseases and prevent associated premature mortality.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is a worldwide public health problem, difficult to diagnose because it is asymptomatic in many people, affecting around 10% of the population in the majority of countries [ 4 ] and closely linked to other major diseases [ 5 ]; CKD is associated with an eightfold to tenfold augmentation in cardiovascular morbimortality and is a risk multiplier in patients with diabetes and/or hypertension [ 6 ]. CKD is defined by a sustained reduction in the estimated Glomerular Filtration Rate (eGFR, <60 mL/min per 1.73 m 2 ) for three or more months, which is accompanied by structural or functional anomalies of kidneys based on urine analysis, biopsy, or imaging [ 7 ].…”
Section: Introductionmentioning
confidence: 99%